Scientific Opinion on Flavouring Group Evaluation 3, Revision 2 (FGE.03Rev2): Acetals of branched‐ and straight‐chain aliphatic saturated primary alcohols and branched‐ and straight‐chain saturated or unsaturated aldehydes, an ester of a hemiacetal and an orthoester of formic acid, from chemical groups 1, 2 and 4 - EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF) (EFSA Journal, 2011)
Abstract The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids of the European Food Safety Authority was requested to evaluate one flavouring substance, acetaldehyde ethyl isopropyl acetal [FL‐no: 06.137], structurally related to the 58 flavouring substances in the Flavouring Group Evaluation 03, in a Revision 2, using the Procedure in Commission Regulation (EC) No 1565/2000. None of the substances were considered to have genotoxic potential. The new substance was along with the remaining 58 substances evaluated through a stepwise approach (the Procedure) that integrates information on structure‐activity relationships, intake from current uses, toxicological threshold of concern, and available data on metabolism and toxicity. The Panel concluded as for the other already evaluated substances that the substance [FL‐no: 06.137] do not give rise to safety concern at its level of dietary intake, estimated on the basis of the MSDI approach. Besides the safety assessment of this flavouring substance, the specifications for the materials of commerce have also been considered, and since the publication of FGE.03Rev1 additional information on chirality on 30 substances is made available and has been incorporated into the present Revision 2 of FGE.03.